Framing the crisis: X/Twitter discourse on Ukrainian war refugees in Poland - Tomasz Piróg; Rafał Olszowski; Piotr Pięta; Tomasz Masłyk (PLoS ONE, 2026)
Social media play a crucial role in shaping public perceptions of migration during crises. This study examines how discourse on Ukrainians in Poland was framed on X/Twitter during the first year of Russia’s full-scale invasion of Ukraine (2022), contributing to research on framing and crisis communication in networked social media environments. Triangulating both quantitative and qualitative methods, we analysed 55,035 Polish-language posts containing the keywords “Ukrainians” and “in Poland.” The analysis combined frame analysis with several complementary methods: stance detection, network analysis, and engagement measurement based on a repost conversion rate. Our findings indicate that while posts displaying negative attitudes dominated in quantity (60%), positive posts had the highest conversion rate. The dominant frames included conflict, international relations and assistance to Ukrainians, highlighting a notable polarization of discourse. Network analysis identified four key user groups with distinct political affiliations. Right-wing government supporters (G1) and the liberal opposition (G4) expressed pro-Ukrainian sentiments, while users with nationalist views (G2) were critical of the influx of Ukrainian migrants. Although Group G2 generated the highest number of posts, their reach was limited due to lower engagement. In contrast, a smaller, politically diverse group (G3) maintained a more neutral stance. These findings demonstrate how integrating frame analysis with network analysis helps capture the relationship between interpretative frames and the structural dynamics of online communication. While solidarity with Ukrainians was strong in 2022, future research should examine how long-term migration processes transform online discourse over time.